Aquisição de linguagem em aluno/Criança com Transtorno do Espectro Autista (TEA) na perspectiva dos docentes: um estudo de caso. - Monte, Márcia Mesquita (2022)
The present study aimed to investigate how the teachers of a school in the Municipal Education Network of Fortaleza/CE understand the issue of language acquisition in students with autism. To this end, we follow the psychoanalytic theory, which expands the conception of language and language through the Lacanian notion of lalangue. We turn to authors such as Saussure, Lacan, Cláudia Lemos, among others. As a methodology, we carried out a qualitative research, of the case study type, having applied a semi-structured questionnaire to a carefully chosen group of four early childhood teachers who had the same student with ASD in common. The results obtained were carefully transcribed in full. As a result, this group of professors exposed their conceptions about the subject, language, language acquisition, strategies and inclusion of this student. The results then indicated a predominance, in the teachers' speech, of a biological-cognitivist-behavioralist conception of the subject, of language and of its acquisition, with repercussions on the notion of inclusion. This dissertation also demonstrated that, by including the notion of lalangue in the scope of language, the consequences are materialized in expanding this field beyond its pre-established limits and increasing the range of possibilities in the relationship between the child (autistic student) and the other (teacher). As seen by the teachers, in order to achieve success in this experience, the training and qualification of teachers need to be addressed and encouraged, because, in this way, the progress of these students in the classroom will be greater.